Assessing Analgesic Use in Patients with Advanced Cancer: Development of a New Scale—The Analgesic Quantification Algorithm. Issue 2 (8th January 2014) - Chung, Karen C.; Barlev, Arie; Braun, Ada H.; Qian, Yi; Zagari, Martin
Abstract Objective Many patients with advanced cancer frequently use analgesic medications for their pain. Systematically assessing and quantifying changes in analgesic use remains challenging in the clinical trials setting. Currently, there is no sensitive scale for categorizing the intensity of analgesic medications to understand the reasons for changes in patient‐reported pain. We assessed whether the Analgesic Quantification Algorithm (AQA) is more sensitive than the World Health Organization Analgesic Treatment Ladder (WHO‐AL) for quantifying analgesic medication use among patients with advanced cancer. Methods An expanded equianalgesic potency conversion table was developed to establish oral morphine equivalents for use in the AQA. Categories of opioid use were selected to increase sensitivity within the higher dose range of opioids and to better capture increases in analgesic dose intensity. The resulting 8‐point AQA scale corresponds to no analgesic use, non‐opioid analgesics, weak opioids only, ≤75 mg, >75–150 mg, >150–300 mg, >300–600 mg, and >600 mg oral morphine equivalents per day. Baseline and 6‐month analgesic data from a clinical trial of cancer patients were compared for each instrument. Results At both time points, the 4‐point WHO‐AL demonstrated a ceiling effect with a clustering of patients in the strong opioid category, whereas the AQA resulted in a distribution of scores throughout the eight categories, including the five strong opioid categories. Conclusions The AQA represents a more sensitive measure of analgesic use than the WHO‐AL, and may better determine whether changes in pain assessments in clinical trials are due to the intervention or changes in analgesic use.